Exploring the Perceptions and Experiences of Local Versus Non-Local Rangers: Insights From Across 11 Countries - Parker, Ben; Singh, Rohit; Hoffmann, Michael; Avino, Felipe Spina; Gajardo, Osvaldo Barassi; Moreto, William; McVey, Drew; Belecky, Mike (Frontiers in Conservation Science, 2022)
Multiple demographic factors can affect ranger experiences and perceptions of their work, including factors like gender, age, and income. Similarly, whether a ranger is local to their conservation area might influence their experiences and perceptions of the work. This premise, however, has received limited attention. In this study we use survey data from across 11 countries to explore how being local to a conservation area might affect ranger experiences and perceptions. We define local rangers as originally being from within 20km of their conservation area. Our findings suggest that being local corresponds to more positive relations with local communities. Our results also imply that whilst being a local ranger might not directly affect job satisfaction, local rangers may well enjoy higher job satisfaction because of how they tend to differ from non-local rangers in other characteristics (e.g., lower formal education; greater access to familial support; more amicable community relations). Moreover, our findings indicate that non-local rangers tend to experience certain symptoms associated with a challenging job (e.g., feeling worn out and emotionally exhausted) more regularly than local rangers, which might correspond to lower welfare. In all, our findings indicate that further, more in-depth research into how the perceptions and experiences of local versus non-local rangers might differ could be useful. Examining the links between being a local ranger and community relations might be especially valuable.